Numerical Solutions of Applications in Ordinary Differential Equation by Implicit Multistep Method - MOHAMAD ZAKI, FARAHIAH 'ADILA; Isa, Syahirbanun (Enhanced Knowledge in Sciences and Technology, 2022)
In this research, an implicit multistep method which is Adams Moulton three step method is used for solving application of first and second order ordinary differential equations (ODEs). The applications in first order ODEs will be solved using Adams Moulton three step method directly and for the application of second order ODEs, at first it will be reduced to the system of first order ODEs, then will be solved using the Adams Moulton three step method. The numerical solution that has been obtained using Adams Moulton three step method is being compare with the exact solution to determine the efficiency and accuracy of the Adams Moulton three step method towards the exact solution. The absolute error is discussed further in this research. The result for the Adams Moulton three step method were obtained using MATLAB 2021. It was observed that the Adams Moulton three step method were efficient in solving application of first and second order ODEs.